Nanocellulose Removes the Need for Chemical Crosslinking in Tannin-Based Rigid Foams and Enhances Their Strength and Fire Retardancy - Missio, André Luiz; Otoni, Caio G.; Zhao, Bin; Beaumont, Marco; Khakalo, Alexey; Kämäräinen, Tero; Silva, Silvia H.F.; Mattos, Bruno D.; Rojas, Orlando J. (ACS Sustainable Chemistry & Engineering, 2022)
Thermal insulation and fire protection are two of the most critical features affecting energy efficiency and safety in built environments. Together with the associated environmental footprint, there is a strong need to consider new insulation materials. Tannin rigid foams have been proposed as viable and sustainable alternatives to expanded polyurethanes, traditionally used in building enveloping. Tannin foams structure result from polymerization with furfuryl alcohol via self-expanding. We further introduce cellulose nanofibrils (CNFs) as a reinforcing agent that eliminates the need for chemical crosslinking during foam formation. CNF forms highly entangled and interconnected nanonetworks, at solid fractions as low as 0.1 wt %, enabling the formation of foams that are ca. 30% stronger and ca. 25% lighter compared to those produced with formaldehyde, currently known as one of the best performers in chemically coupling tannin and furfuryl alcohol. Compared to the those chemically crosslinked, our CNF-reinforced tannin foams display higher thermal degradation temperature (peak shifted upward, by 30-50 °C) and fire resistance (40% decrease in mass loss). Furthermore, we demonstrate partially hydrophobized CNF to tailor the foam microstructure and derived physical-mechanical properties. In sum, green and sustainable foams, stronger, lighter, and more resistant to fire are demonstrated compared to those produced by formaldehyde crosslinking.
Created from Fastlane, Scopus look-up
Keywords: cellulose nanofibrils; condensed tannins; nonflammable foams; nonstructural building materials; solid foams; thermal insulation